2013
DOI: 10.3390/s131012744
|View full text |Cite
|
Sign up to set email alerts
|

Tip-Enhanced Raman Imaging and Nano Spectroscopy of Etched Silicon Nanowires

Abstract: Tip-enhanced Raman spectroscopy (TERS) is used to investigate the influence of strains in isolated and overlapping silicon nanowires prepared by chemical etching of a (100) silicon wafer. An atomic force microscopy tip made of nanocrystalline diamond coated with a thin layer of silver is used in conjunction with an excitation wavelength of 532 nm in order to probe the first order optical phonon mode of the [100] silicon nanowires. The frequency shift and the broadening of the silicon first order phonon are ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…This is accomplished using the apex of a tip as a single plasmonic scatterer, and moving it in a controlled manner with respect to the sample. The power of TERS to improve the spatial resolution was demonstrated on single nanowires and crystallites [26][27][28] with a resolution comparable to that of AFM imaging. Raman and photoluminescence spectra of CdSe nanowires were investigated as well, achieving optical resolution below AFM resolution achieved in the same experiment due to square-law field dependence of both the excitation and the emission rates 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…This is accomplished using the apex of a tip as a single plasmonic scatterer, and moving it in a controlled manner with respect to the sample. The power of TERS to improve the spatial resolution was demonstrated on single nanowires and crystallites [26][27][28] with a resolution comparable to that of AFM imaging. Raman and photoluminescence spectra of CdSe nanowires were investigated as well, achieving optical resolution below AFM resolution achieved in the same experiment due to square-law field dependence of both the excitation and the emission rates 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…8 (2) Presence of defects leads to a reduction of phonon lifetime, leading to a symmetric broadening of the Raman peaks, as phonon lifetime is inversely proportional to the natural line-width of the Raman peaks. 9 the values of elements of the polarizability tensors related to vibrational modes involving these bonds, which in turn leads to changes in intensity of the corresponding peaks. 11 In this framework, this work presents a detailed analysis of the impact of different kinds of compositionally induced defects in the Raman spectra from device-grade CZTSe absorbers (maximum efficiency 6.9%).…”
mentioning
confidence: 99%
“…The aging of polymeric surfaces using IR and Raman images was performed by Eder et al 90 In this work, the complementarity of the techniques was demonstrated, with IR being more suitable for the identification of organic molecules (especially when carbonyl, hydroxyl and amine groups are present) and Raman for unsaturated compounds (such as conjugated and aromatic ones), as well as inorganic materials. An example of the use of TERS in the characterization of materials can be seen in the work of Kazemi-Zanjani et al, 91 in which it was used for the characterization of silicon nanowires to determine if they were on their overlapping or in isolation. It was possible to find subtle spectral changes depending on the position of the nanowires due to better spatial resolution.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…The difference in a certain area was also demonstrated when using the TERS technique with or without the AFM tip. 91…”
Section: Materials Characterizationmentioning
confidence: 99%